HALAL INDUSTRY IN INDONESIA: OPPORTUNITIES, CHALLENGES AND STRATEGIES: HALAL INDUSTRY IN INDONESIA: OPPORTUNITIES, CHALLENGES AND STRATEGIES - Syamsiyah, Nur; Ardana, Yudhistira (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2022)
This study aims to explain how the opportunities, challenges and strategies can be carried out by the Halal Industry in Indonesia. The method used in this study is a qualitative descriptive method using the library method. This study uses secondary data obtained through scientific articles and other relevant documents. The data obtained were analyzed using qualitative analysis through data reduction, categorization and verification. This research finds that Indonesia has tremendous opportunities to develop the halal industry. These opportunities include the halal food sector, the Islamic finance sector, the halal tourism sector, and the Muslim fashion sector. However, there are external and internal challenges in the development of the halal industry, external challenges, namely the number of competing countries, the absence of a globally agreed halal certificate and the incompatibility of Muslim countries in setting halal product standards. And internal challenges, namely the lack of halal awareness among the Indonesian people and the problems of Law Number 33 of 2014 concerning Halal Product Guarantee, as well as the low awareness of the Indonesian people to compete. As for the challenges of the halal industry in Indonesia; many competitors from the international world, there is no halal certification that applies nationally, understanding of the concept of halal is still lacking, socialization is still lacking, laws and regulations are not perfect. Strategies that can be done; developing superior human resources, reliable strategies for socializing halal products and others.